Decreased number of myeloid-derived suppressor cells in the placental trophoblast of gestational diabetes mellitus. Possible role of leptin - Malika Tami; Lourdes Hontecillas-Prieto; Daniel García-Domínguez; Rocío Flores-Campos; Teresa Vilariño-García; Flora Sánchez-Jiménez; Pilar Guadix; José L. Dueñas; Carlos Jiménez-Cortegana; Luis de la Cruz-Merino; Antonio Pérez-Pérez; Víctor Sánchez-Margalet (Immunobiology)
Gestational diabetes mellitus (GDM) is the most common complication of pregnancy and significantly increases both maternal and fetal morbidity and mortality. Inflammation is a hallmark of GDM, and placental inflammation may play a key role in the pathophysiology of the disease. Myeloid-derived suppressor cells (MDSCs), which are innate immunosuppressive, are thought to contribute to feto-maternal tolerance. In normal pregnancies, elevated levels of MDSCs have been observed in both peripheral and umbilical cord blood. Our hypothesis postulates that trophoblasts from placentas belonging to women with GDM may have lower levels of MDSCs compared to trophoblasts from placentas originating from healthy pregnancies. Furthermore, since leptin is overexpressed in the placenta of GDM patients, we hypothesized that leptin might contribute to the reduction of MDSCs. To test this, we investigated the in vitro effects of leptin on MDSC levels in isolated peripheral blood leukocytes after 24 h of incubation. Our findings indicate that trophoblasts from placentas from women with GDM contain a lower percentage of MDSCs compared to trophoblasts from healthy pregnancies. In addition, in vitro studies demonstrated that leptin reduces the number of MDSCs in peripheral blood leukocytes.In conclusion, MDSCs are decreased in placentas from pregnancies with GDM, and leptin appears to reduce the number of MDSCs in leukocytes isolated in vitro. Increased leptin expression in trophoblasts from placentas of women with GDM may contribute to the lower levels of MDSCs, potentially playing a role in placental inflammation. However, further investigations are required to fully elucidate this mechanism.